The EU Budget and Common Agricultural Policy Beyond 2020: Seven More Years of Money for Nothing? - Friedrich Heinemann; Stefani Weiss (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
The European Commission's proposals for the post-2020 Common Agricultural Policy (CAP) are under discussion, and these cautious reform ideas have set the parameters for upcoming negotiations. CAP will continue to have a two-pillar structure of direct payments and rural development, with a seven-year budget of exteuro365 billion. As before, almost three-quarters of the budget - exteuro265 billion - is reserved for direct payments to farmers. However, `European added value' must be urgently applied to CAP, say Friedrich Heinemann and Stefani Weiss, who have developed a series of recommendations to justify direct payments in their latest report for EconPol.
Keywords: 330